Remediation of lead-contaminated sludge for soil conditioning using waste lemon peel - Duru, Chinonye; Ibrahim, Fatima Badiru; Dandajeh, Aliyu Adamu (Journal of Applied Materials and Technology, 2024)
Enhancing soil fertility, organic matter, and nutrient content through sludge application to agricultural land is a promising approach to improve crop efficiency. Waste lemon peel, considered agricultural waste, has potential as a remediation agent for lead-contaminated sewage. This study examines the physical and chemical properties of lemon peel extract to evaluate its potential as a substitute for commercial fertilizer. The response surface methodology was employed to investigate the factors influencing the process. A multi-objective numerical optimization technique based on the desirability function was used to identify the optimal conditions for lead removal efficiency in contaminated wastewater. The study focuses on parameters such as pH, extractant concentration, and contact time. The optimization analysis achieved a maximum removal efficiency (ER) of 94.42% at a pH of 5.0, an extractant concentration of 20 g/L, and a contact time of 135 minutes. Under optimal conditions, the highest lead removal efficiency was 90.50%, while the lowest efficiency observed was 47.0%. The findings of this study underscore the significant issue of environmental contamination, particularly with heavy metals like lead, and highlight the necessity for sustainable and eco-friendly solutions. The effective use of lemon peel extract demonstrates its potential as a viable alternative for remediating lead-contaminated wastewater.